Pendampingan UMKM dalam Pembuatan Packaging Inovatif Kentang Mustofa dan Optimalisasi Penjualan untuk Meningkatkan Daya Jual Produk - Deni Ramdhani; Rifka Agustianti; Rahmi Mudia Alti; Yoana Nurul Asri; Ike Yuni Wulandari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
Packaging is an important element in building a product's brand. Packaging plays an important role because it will always be associated with the packaged product and represents the sales value and image of the product. Product sales will increase if the packaging is attractive, and the product image is closely tied to consumers' opinions about the product. The method used in this activity is training, specifically direct support to partners. The overall objective of this activity is to provide training on how economic entities such as small and medium enterprises can develop product packaging so that the products produced are in high demand by consumers so that they can develop good business and can contribute to economic development. In addition, it also supports sales optimization to increase sales. Through this activity, partners share knowledge about packaging design and selling products online. Partners also receive guidance to improve their skills in presenting more attractive product photos. With changes in packaging design and sales methods, partner revenue has increased, and product shelf life has also increased. Scholars as PKM implementers can deploy their expertise to collaborate with the community.